Cortical complexity in bipolar disorder applying a spherical harmonics approach. (30th May 2017) - Nenadic, Igor; Yotter, Rachel A.; Dietzek, Maren; Langbein, Kerstin; Sauer, Heinrich; Gaser, Christian
Abstract: Recent studies using surface-based morphometry of structural magnetic resonance imaging data have suggested that some changes in bipolar disorder (BP) might be neurodevelopmental in origin. We applied a novel analysis of cortical complexity based on fractal dimensions in high-resolution structural MRI scans of 18 bipolar disorder patients and 26 healthy controls. Our region-of-interest based analysis revealed increases in fractal dimensions (in patients relative to controls) in left lateral orbitofrontal cortex and right precuneus, and decreases in right caudal middle frontal, entorhinal cortex, and right pars orbitalis, and left fusiform and posterior cingulate cortices. While our analysis is preliminary, it suggests that early neurodevelopmental pathologies might contribute to bipolar disorder, possibly through genetic mechanisms. Highlights: Cortical complexity based on fractal dimensions is a novel approach to brain morphometrics. Cortical complexity in bipolar disorder is altered in frontal and entorhinal areas. Bipolar disorder might be associated with early neurodevelopmental pathology.